Generation of the change DEM from the new global TanDEM-X Acquisitions (2017-2019) - Lachaise, Marie; Bachmann, Markus; Fritz, Thomas; Huber, Martin; Schweißhelm, Barbara; Wessel, Birgit (2019)
With the global TanDEM-X DEM generation being finished in 2016, the mission is now acquiring a new dataset to provide an independent DEM, the so-called “TanDEM-X Change DEM”. It is based on a completely new dataset acquired from 2017 - 2019 in contrast to the acquisitions for the global DEM between 2010 and 2015 in the aim to characterize terrain changes. It benefits from improvements in the acquisition planning process and in the data processing which enable to achieve reliable DEM data of high accuracy with fewer acquisitions. For this goal, the use of an edited TanDEM-X DEM as "starting point" for the processing is mandatory. Detectable 3d elevation changes are presented exemplary in Indonesian forest and on an outlet glacier in Antarctica.